Occupational stress and associated risk factors among 13,867 industrial workers in China - Yan, Tenglong; Ji, Fang; Bi, Mingli; Wang, Huining; Cui, Xueting; Liu, Baolong; Niu, Dongsheng; Li, Leilei; Lan, Tian; Xie, Tingting; Wu, Jie; Li, Jue; et al. (Frontiers in Public Health, 2022)
Objective: Occupational stress is a critical global public health problem. We aimed to evaluate the prevalence of occupational stress among the workers in the electricity, heat, gas, water production, and supply (EHGWPS), the manufacturing and the transportation industries in Beijing, China. We explored the demographic differences in occupational stress status among workers in industrial enterprises. Methods: A cross-sectional study was conducted on 13,867 workers. The self-administered New Brief Job Stress Questionnaire was used to evaluate high occupational stress status, which includes four sub-dimensions (job stressors, stress response, social support, job stressors and social support). Multiple regression and logistic regression models were used to estimate the association between high occupational stress and the four occupational stress sub-dimensions with risk factors. Results: A total of 13,867 workers were included. The prevalence of high occupational stress was 3.3% in the EHGWPS industries, 10.3% in manufacturing, and 5.8% in transportation. The prevalence of high occupational stress was higher than in the other two categories (p < 0.05) in manufacturing industries. Logistic regression analysis showed that male workers with lower educational status, more job experience, and working in manufacturing were vulnerable to high occupational stress. Further analysis of the four occupational stress sub-dimensions showed that males, older adult workers, workers with lower educational levels, and longer working time were associated with higher scores in job stressors, stress response, social support, and job stress and social support (all p < 0.05). Moreover, divorced or widowed workers had higher occupational stress scores. Conclusions: Male workers with lower educational level and longer working time may have an increased risk of occupational stress.